IBM Tivoli storage resource manager : a practical introduction - Brooks, Charlotte (IBM redbooks., 2003)
Storage growth continues to accelerate, and the cost of disk can approach 80% of total system hardware costs. Yet, the storage in most businesses is typically only about 50% used. How can you take control of your storage assets to render utilization more efficient, and make the most of your storage dollars? IBM Tivoli Storage Resource Manager helps you discover, monitor, and create enterprise policies for your filesystems and databases. You will find out where all your storage is going and be able to act intelligently on this information. Application availability is improved because you will have early warnings when filesystems are running out of space. If you are thinking about server consolidation, you can use IBM Tivoli Storage Resource Manager to help efficiently utilize your accumulated storage resources. This IBM Redbooks publication shows how to install, configure, and protect the IBM Tivoli Storage Resource Manager environment; how to create policies; how to define automated actions like scripts or SNMP events when policies are violated; and how to produce detailed, meaningful storage reports. This book is intended for those who want to learn more about IBM Tivoli Storage Resource Manager and for those who are about to implement it. The second edition of this book is updated for IBM Tivoli Storage Resource Manager Version 1.2 Please note that the additional material referenced in the text is not available from IBM.